The Writing of a Case History in a Neurological Department with Computer Application - Hofferberth, B.; Gottschaldt, M. (Methods of Information in Medicine, 1978)
A program is described which is used daily for the elaboration of case histories in a neurological department. Using a dialogue procedure, the input is done by the physician himself after taking the case history and the clinical findings on admission. The system compiles the case history from stored texts for the normal findings and entered texts for the pathological findings. The completeness and the standardization of the case history within the clinic is an essential benefit. In addition, statistical analyses are possible using the case history as original material.
Keywords: Neurological Case History; Automation of Writing; Computer Application